Determination of buprofezin, pyridaben, and tebufenpyrad residues by gas chromatography mass-selective detection in clementine citrus - Cabras, P.; Angioni, A.; Garau, V. L.; Melis, M.; Pirisi, F. M.; Cabitza, F.; Dedola, F.; Navickiene, S. (Amer Chemical Soc, 1998)
A gas chromatography-mass-selective (GC-MS) detection method to determine buprofezin, pyridaben, and tebufenpyrad on the pulp, peel, and whole fruit of clementines is described. The extraction/partition procedure was performed in one step and no cleanup was necessary with the GC-MS in the SIM-mode pesticide determination. Recovery ranged from 75 to 124% with coefficients of variance ranging between 1 and 13%. The limit of determination was 0.01 mg/kg for all pesticides. The field trials showed a similar degradative behavior for all active ingredients (AI), with a great residue decrease during the first week and stability in the second. Just after treatment buprofezin and tebufenpyrad showed lower residues than the maximum residue limit (MRL) fixed in Italy, while pyridaben was below the MRL after a week.
Keywords: residues; GC-MS; buprofezin; pyridaben; tebufenpyrad; clementine